Calcium carbonate: controlled synthesis, surface functionalization, and nanostructured materials - Niu, Yu-Qin; Liu, Jia-Hui; Aymonier, Cyril; Fermani, Simona; Kralj, Damir; Falini, Giuseppe; Zhou, Chun-Hui (Chemical Society reviews, 2022)
Calcium carbonate (CaCO 3 ) is an important inorganic mineral in biological and geological systems. Traditionally, it is widely used in plastics, papermaking, ink, building materials, textiles, cosmetics, and food. Over the last decade, there has been rapid development in the controlled synthesis and surface modification of CaCO 3 , the stabilization of amorphous CaCO 3 (ACC), and CaCO 3 -based nanostructured materials. In this review, the controlled synthesis of CaCO 3 is first examined, including Ca 2+ -CO 3 2− systems, solid-liquid-gas carbonation, water-in-oil reverse emulsions, and biomineralization. Advancing insights into the nucleation and crystallization of CaCO 3 have led to the development of efficient routes towards the controlled synthesis of CaCO 3 with specific sizes, morphologies, and polymorphs. Recently-developed surface modification methods of CaCO 3 include organic and inorganic modifications, as well as intensified surface reactions. The resultant CaCO 3 can then be further engineered via template-induced biomineralization and layer-by-layer assembly into porous, hollow, or core-shell organicinorganic nanocomposites. The introduction of CaCO 3 into nanostructured materials has led to a significant improvement in the mechanical, optical, magnetic, and catalytic properties of such materials, with the resultant CaCO 3 -based nanostructured materials showing great potential for use in biomaterials and biomedicine, environmental remediation, and energy production and storage. The influences that the preparation conditions and additives have on ACC preparation and stabilization are also discussed. Studies indicate that ACC can be used to construct environmentally-friendly hybrid films, supramolecular hydrogels, and drug vehicles. Finally, the existing challenges and future directions of the controlled synthesis and functionalization of CaCO 3 and its expanding applications are highlighted. Various new strategies have been recently developed to produce CaCO 3 micro-/nanoparticles with controlled size, morphology, polymorphism and crystallinity, which are then surface modified, functionalized and hierarchically assembled to yield medical, environmental, and energy materials.